Penerapan Pendekatan Problem Solving Untuk Meningkatkan Hasil Belajar Siswa Pada Pembelajaran IPA Kelas IV SDN 002 Langgini Kabupaten Kampar - Yenni Fitra Surya (Prodi PGSD FIP UNM, 2017)
This study originated from the fact low yields and students learn science in understanding the science learning difficulties in class IV SDN 002 Langgini. This is because the teachers do not give lessons in accordance with the concrete situation of the students. One solution to overcome this problem is to use a problem-solving approach.approach Problem solving is an approach to developing reasoning power, skill, and creativity in problem-solving so that students can improve learning outcomes, thus the purpose of this study was to describe the learning outcome in the fourth-grade science students with the approach. problem solvingThis study uses qualitative and quantitative approach to the form of research is classroom action research. This study was conducted in two cycles. The research was conducted in the fourth-grade SDN 002 Langgini. Collecting data in this study using techniques of documentation, observation, and tests. Data were analyzed using qualitative and quantitative data analysis. Improved student learning outcomes in science learning with approach problem-solving in each cycle can be seen from the average value of 70.1 with a percentage of completeness 71% in the first cycle and the average value of 83.1 with a percentage of completeness 93% in the second cycle.